Functional differences in transport properties of natural HKT1;1 variants influence shoot Na+ exclusion in grapevine rootstocks. Issue 3 (21st November 2017) - Henderson, Sam W.; Dunlevy, Jake D.; Wu, Yue; Blackmore, Deidre H.; Walker, Rob R.; Edwards, Everard J.; Gilliham, Matthew; Walker, Amanda R.
Summary: Under salinity, Vitis spp. rootstocks can mediate salt (NaCl) exclusion from grafted V. vinifera scions enabling higher grapevine yields and production of superior wines with lower salt content. Until now, the genetic and mechanistic elements controlling sodium (Na + ) exclusion in grapevine were unknown. Using a cross between two Vitis interspecific hybrid rootstocks, we mapped a dominant quantitative trait locus (QTL) associated with leaf Na + exclusion ( NaE ) under salinity stress. The NaE locus encodes six high‐affinity potassium transporters (HKT). Transcript profiling and functional characterization in heterologous systems identified VisHKT1;1 as the best candidate gene for controlling leaf Na + exclusion. We characterized four proteins encoded by unique VisHKT1;1 alleles from the parents, and revealed that the dominant HKT variants exhibit greater Na + conductance with less rectification than the recessive variants. Mutagenesis of VisHKT1;1 and TaHKT1.5‐D from bread wheat, demonstrated that charged amino acid residues in the eighth predicted transmembrane domain of HKT proteins reduces inward Na + conductance, and causes inward rectification of Na + transport. The origin of the recessive VisHKT1;1 alleles was traced to V. champinii and V. rupestris . We propose that the genetic and functional data presented here will assist with breeding Na + ‐tolerant grapevine rootstocks.